The Sydney North West Rail Link project tunnelling challenge with four double shield TBMs. Issue 5 (October 2015) - Camus, Thomas; Therville, Fabrice
Abstract NFM Technologies has designed and delivered four 6.99 m‐diameter Double Shield TBMs that are excavating the North West Rail Link project, an extension to the Sydney rapid transit network. The project is led by a consortium comprising Thiess, John Holland and Dragados, acting on behalf of the Government of New South Wales Transport Authority. Altogether, the TBMs will build 15 km of twin tunnels in rock that is mainly formed of abrasive sandstone. TBMs 1 and 2 bore the 9 km section between the Bella Vista and Cherrybrook stations, while the remaining 6 km from Cherrybrook to the Epping interchange are bored by TBMs 3 and 4. In this paper, we focus on the achieved performance of the 4 TBMs after approximately 50% completion. We analyse their variations in terms of excavation speed and consumption of disc cutters against the geology and geotechnical characteristics along the tunnel route. We discuss the overall production data and specific aspects of this hard rock urban tunnel project.